1988
DOI: 10.1103/physreva.38.2189
|View full text |Cite
|
Sign up to set email alerts
|

Comment on ‘‘Lifetime of excited atomic states’’

Abstract: We show that the two-photon nonresonant contributions to the lifetime of excited 3s and 3d states of hydrogen, as given by a formula recently derived by Cresser et al. [Phys. Rev. A 33, 1677 (19S6)],can be evaluated in an economic way using the analytic expressions of the amplitudes of 3s-1s and 3d-1s two-photon transitions. Our numerical evaluation confirms the numbers given by Cresser et al. In a recent paper Cresser et al. ' have considered the contribution of two-photon emission to the lifetime of an exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 3 publications
2
35
0
Order By: Relevance
“…In order to avoid problems with non-integrable singularities, the authors of [9] Although the results presented in Refs. [9,10] are in mutual agreement, they are both based on the interpretation of the two-photon decay rate Γ…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…In order to avoid problems with non-integrable singularities, the authors of [9] Although the results presented in Refs. [9,10] are in mutual agreement, they are both based on the interpretation of the two-photon decay rate Γ…”
Section: Introductionmentioning
confidence: 75%
“…One of these problems, which currently attracts a lot of interest, concerns those two-photon transition from highly excited states to the ground state which pass through an intermediate state with a lower energy than the initial state of the two-photon process [9,10] and can alternatively decay to the groundstate via two (or more) sequential one-photon emissions. Such a transition leads to resonance peaks in the energy spectrum of the coherently emitted photons from the two-photon decays which are located at the energies corresponding to the (real) intermediate states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…explicitly neglecting the transition via the intermediate 3p-state, we can reproduce their values for the non-resonant contribution to the two-photon decay rates of the 3s → 1s and 3d → 1s transitions. Later Florescu et al (1988) computed these values again within the framework of Cresser et al (1986) and A nr,Cr 3d→1s = 0.131814 s −1 ) up to all given figures. Although the discussion in the previous sections has already shown that these values probably have no direct relation to the total corrections in the lifetime of the level due to the two-photon process, we computed them to check our own computational procedure.…”
Section: The Non-resonant Contributionmentioning
confidence: 99%
“…At nearly the same time as the arrival of the paper [18], the cascade problem was discussed also for the ns (n > 2), nd transitions in the hydrogen atom [23,24]. In these works the pure two-photon contribution was obtained simply by omitting the resonant (singular) terms responsible for the cascades.…”
Section: Introductionmentioning
confidence: 99%